Addressing the dilemmas of measuring amylose in rice - Fitzgerald, MA; Bergman, C.J.; Resurreccion, AP; Moller, J; Jiménez, R.; Reinke, RF; Martin, M.; Blanco, P.; Molina, F.; Chen, M.H.; Kuri, Victoria Eugenia; Romero, M.V.; et al. (Wiley, 2009)
Amylose content is a parameter that correlates with the cooking behavior of rice. It is measured at the earliest possible stages of rice improvement programs to enable breeders to build the foundations of appropriate grain quality during cultivar development. Amylose is usually quantified by absorbance of the amylose‐iodine complex. The International Network for Quality Rice (INQR) conducted a survey to determine ways that amylose is measured, reproducibility between laboratories, and sources of variation. Each laboratory measured the amylose content of a set of 17 cultivars of rice. The study shows that five different versions of the iodine binding method are in use. The data show that repeatability was high within laboratories but reproducibility between laboratories was low. The major sources of variability were the way the standard curve was constructed and the iodine binding capacity of the potato amylose used to produce the standard. Reproducibility is much lower between laboratories using a standard curve of potato amylose alone compared with those using calibrated rice cultivars. This study highlights the need to standardize the way amylose is measured, and presents research avenues for doing so.